2021
DOI: 10.5296/ber.v11i2.18451
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Savings Group on the Nutritional and Economic Wellbeing of Rural Households: The Case of World Vision’s Savings for Transformation (S4T) in Zambia

Abstract: Smallholders and the poor populations, especially in rural areas, tend to have little or no access to formal credit, which limits their capacity to invest in the technologies and inputs they need to increase their yields and incomes and reduce hunger and poverty. This mainly arises because financial institutions interested in serving this market face a myriad of risks and challenges associated with agricultural production and lending, including seasonality and the associated irregular cash flows, high transact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…This adds to the empirical evidence that women empowerment and autonomy improves nutritional status of mothers, their children, and other members of the household [ [33] , [34] , [35] ]. Literature shows that social safety nets increase income resilience, especially for the vulnerable groups, which leads to spending more on food and positive change in food consumption for pregnant women, lactating mothers, and children [ 10 , 36 ] through improved access to resources [ 37 ]. However, women empowerment is a multidimensional domain where different domains, such as income, education, gender parity, agricultural production, and group membership empowerment, may influence the nutritional status through various mechanisms [ 26 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This adds to the empirical evidence that women empowerment and autonomy improves nutritional status of mothers, their children, and other members of the household [ [33] , [34] , [35] ]. Literature shows that social safety nets increase income resilience, especially for the vulnerable groups, which leads to spending more on food and positive change in food consumption for pregnant women, lactating mothers, and children [ 10 , 36 ] through improved access to resources [ 37 ]. However, women empowerment is a multidimensional domain where different domains, such as income, education, gender parity, agricultural production, and group membership empowerment, may influence the nutritional status through various mechanisms [ 26 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Zambia, many nonprofit organizations, including; CRS, World Vision, and CARE, utilize the VSLA model and have been adopted in various rural communities (Bwalya & Zulu, 2021). This has proved that this model indeed provides the much-needed support and benefits that improve families' income sources and living standards.…”
Section: Village Savings and Loan Associations (Vsla)mentioning
confidence: 99%
“…According to the goal of World Vision Zambia's Saving for Transformation (S4T) program, informal financial services contribute to improving the resilient livelihood for 45,378 households (232,060 people) in Zambia alone by the end of 2021 (Bwalya & Zulu, 2021). Financial inclusion beyond livelihood's improvement is a key output of various savings groups in addition to providing other financial services to entrepreneurs such as micro-insurance.…”
Section: Introductionmentioning
confidence: 99%
“…They are formed by community members who agree to save part of their earnings and have their own guiding principles. They also have different functions including providing credit to members with minimum interest, funeral grants, and giving cash to members when they are sick [17]. Evidence has shown that savings group have functioned quiet well in improving social welfare services including improving the capacity to save for emergences among community members [18].…”
mentioning
confidence: 99%
“…Evidence has shown that savings group have functioned quiet well in improving social welfare services including improving the capacity to save for emergences among community members [18]. In terms of healthcare, communities' members have reported to have used part of these savings for transports, purchase of foods as well as other supplies [17]. However, there is little evidence on how they can and should be used in the collection of premiums towards nancing of the NHI.…”
mentioning
confidence: 99%